Consumer food storage practices and methods at the household-level: a community study in Ghana - Afriyie, Ebenezer; Zurek, Monika; Asem, Freda E.; Okpattah, Bernard; Ahiakpa, John K.; Zhu, Yong-Guan (Frontiers in Sustainable Food Systems, 2023)
Introduction Household-level food storage can make food available to consumers, and promotes food security. Nevertheless, attention is mostly devoted to enhancing food storage at the farmer and national levels, neglecting the household level. It is therefore critical to assess food storage practices of households. This study examined food storage practices of households, evaluated expert opinions on household-level food storage, and assessed the effect household characteristics has on food storage and food security. Methods Dzorwulu and Jamestown communities in Accra, Ghana, were chosen as the study locations. The study consisted of a survey, expert interviews and structural equation modeling. For the survey, 400 food household heads selected using systematic sampling method responded to a semi-structured questionnaire. Seventeen (17) experts were also purposively sampled and interviewed. Results and Discussion The results showed that, most households stored foodstuffs they often consumed, with generally low storage of fruits and vegetables. Perishable foods such as cassava, tomato, yam, and banana were stored by 37.8, 42, 38.3 and 43.8% of households, respectively, for 1–3 days. Households often stored food within a period of 2 weeks, due to poor storage facilities and lack of food storage knowledge. About 85.8% of households had never received training on food storage. Most households used baskets, bowls, sacks and polyethylene bags to store food at home, and some used refrigerators and deep freezers. Regarding the link between food storage and food security, household heads’ income showed a significant positive moderating effect (p ≤ 0.01), households’ socioeconomic status had a positive effect, while household size indicated a significant negative moderating effect (p ≤ 0.01). The experts asserted that, household-level food storage enhances food security and food safety, and reduces food expenditure and food wastage. The limited food storage knowledge of households should be a basis for intervention to enhance proper food storage practices within households.